Original article MRI assisted cervix cancer brachytherapy pre-planning, based on insertion of the applicator in para-cervical anaesthesia: preliminary results of a prospective study - Petric, Primoz; Hudej, Robert; Music, Maja (Journal of Contemporary Brachytherapy, 2009)
Purpose: To report on preliminary results of a prospective study on MRI-assisted cervix cancer brachytherapy pre-planning. Material and methods: In six locally advanced cervix cancer patients, five days before the first brachytherapy fraction, tandem & ring applicator was inserted under para-cervical anaesthesia, MRI performed and applicator removed. Procedure-time and patient-tolerability were recorded. High risk CTV and organs at risk were delineated, virtual needles placed and dose planning performed. At brachytherapy, insertion was carried out under subarachnoidal anaesthesia, according to pre-planned geometry. Pre-planned and actual needle positions and DVH parameters were compared. Results: The procedure was well tolerated and short. All inserted needles were inside high risk CTV and outside organs at risk. Differences in pre-planned and actual DVH parameters and implant geometry were small. Conclusions: The procedure was well tolerated and feasible. Pre-planned geometry could be reproduced thoroughly at brachytherapy application.